Latin America : a new interpretation - Whitehead, Laurence (Studies of the Americas., 2006)
This innovative contribution to comparative area studies evaluates Latin America's distinctiveness, and shows how 'large regions' can be compared. The overwhelming impact of Europe followed by precocious independence produced an exceptional outward orientation, which has prompted successive waves of reform 'from above and without', often resisted and superceded rather than fully assimilated. This book explores the resulting patterns that can be observed in multiple domains, through the optic of a 'mausoleum of modernity.' By applying this perspective to state organization, the politics of expertise, privatization, poverty and inequality, and citizenship insecurity, it generates an overall new interpretation of Latin America's regional distinctiveness.